Disinformation in the digital age: addressing the post-truth formula in political communication - Guadarrama Torres, Jorge Jair; Álvarez Garzón, Lorena Catherine; Molina Picazo, Miguel Antonio (Scripta Mundi, 2025)
This article seeks to analyze disinformation in the face of political communication, exacerbated by a post-truth formula. This research explores how disinformation and post-truth spread in the current political context, analyzing their impact on public opinion, democratic debate and trust in institutions. It highlights as one of the important factors opinorophobia and the need to promote media literacy, critical thinking and transparency in political communication to counteract disinformation and strengthen democracy in the digital age. The methodology that was addressed was through a case study of recent political campaigns. In addition, examples of fake news, polarizing speeches and emotional manipulation strategies used in these campaigns are examined, along with the compilation of opinion articles and reflections of the authors for the construction of the concept of "opinorophobia" which is defined as the fear of expressing opinions in a context of polarization and media lynching.
Keywords: disinformation; government communication; opinorophobia; politics; post-truth